Controversies in the efficacy of adjuvant chemotherapy in different epithelial ovarian carcinoma histologies - Ece Esin; İrem Bilgetekin; Fatma Buğdaycı Başal; Ayşe Ocak Duran; Umut Demirci; Berna Öksüzoğlu (Journal of Oncological Sciences)
Aim: In this retrospective study, the efficacy of adjuvant chemotherapy and its contribution to prognosis were investigated in patients diagnosed with different subgroups of ovarian carcinoma at stages 1–3. Material and Method: Epithelial ovarian carcinoma cases treated at Ankara Oncology Training and Research Hospital of Health Sciences University between January 2014 and May 2018 were retrospectively analyzed. Results: A total of 145 patients were diagnosed and treated for EOC during the study period. According to histopathological subgroups, serous EOC was the most common (84.8%), followed by endometrioid (6.6%), mucinous (4.8%) and clear cell types (3.8%). Local recurrence and distant recurrences were observed in 39 (43.8%) and 7 (7.9%) cases in the serous EOC group, respectively. The median follow-up was 39 months (10–217 months). Median survival was 91.4 months (58.9–123.9 months) in the whole group and 100.9 months in serous EOC. Median survival in mucinous EOC was 26.2 months, whereas median survival in endometrioid EOC and clear cell EOC were not reached. A statistically significant difference of survival was found between serous and mucinous types of tumors (p: 0.04. Conclusions: According to the results of this study examining the survival outcomes of epithelial ovarian cancer subtypes after chemotherapy, there was a statistically significant difference between the prognosis of different epithelial ovarian cancer cases after taxane and platinum-containing adjuvant chemotherapy. Mucinous type of tumors exhibited less overall survival compared to endometrioid and clear cell types which needs to be confirmed with prospective clinical trials. Keywords: Epithelial ovarian carcinoma, Serous, Mucinous, Adjuvant treatment, FIGO stage